The Forensic toxicology: importance in crime investigation: Asif Ibrahim, Syed Khurram Hassan - Asif Ibrahim; Syed Khurram Hassan (International Journal for Electronic Crime Investigation, 2022)
By using chemical and analytical techniques, forensic toxicology contributes to the establishment of facts in forensic investigations by studying the medical and legal aspects of the detrimental effects of a drug on organisms. Forensic practices are crucial in cases of deadly poisoning and those that could be connected to criminal activity. In most murder, suicide, or accident cases, poisons are discovered. They are a crucial component of the silent weapon that silently and covertly ends life. The current study is focused on the field of forensic chemistry and toxicology, which is entirely centered on the introduction, categorization, effects, and influencing factors of poisons, as well as their detection and testing. This article’s goal is to examine how they behave and perform after they enter the human body. Poisons have serious effects and might even be fatal if not treated appropriately.